Situational Identity: A Study of Identity Communication in Bengkulu City - Alfarabi; Aldila Vidianingtyas Utami; Puji Haryadi Mulyana Sukma (DAWUH : Islamic Communication Journal, 2025)
This study examines the issue of identity confusion among the people of Bengkulu, which is characterized by a heterogeneous population. The research is based on field phenomena where many migrants and their descendants still experience uncertainty in expressing their cultural identity. This research uses a descriptive qualitative approach focused on the community of Bengkulu City. These findings are analyzed using Michael Hecht’s Communication Theory of Identity (CTI), which conceptualizes identity as something that is formed, negotiated, and maintained through communication across four interpenetrative layers. The research informants consist of community leaders and academics who meet the established criteria. Data were collected through in-depth interviews and focus group discussions. The results were analyzed using the Miles and Huberman approach and validated through source triangulation. The findings reveal that identity confusion is particularly evident among the younger generation whose parents are not originally from Bengkulu City. One way individuals attempt to construct their identity is by aligning themselves with one of the available "stocks of identity" in Bengkulu. These include: first, identifying as Orang Bengkulu (People of Bengkulu) and second, as Orang Melayu Bengkulu (Ethnic Malay of Bengkulu). .